Urolithins: a Comprehensive Update on their Metabolism, Bioactivity, and Associated Gut Microbiota - García‐Villalba, Rocío; Giménez‐Bastida, Juan Antonio; Cortés‐Martín, Adrián; Ávila‐Gálvez, María Ángeles; Tomás‐Barberán, Francisco A.; Selma, María Victoria; Espín, Juan Carlos; González‐Sarrías, Antonio (Molecular nutrition & food research, 2022)
Urolithins, metabolites produced by the gut microbiota from the polyphenols ellagitannins and ellagic acid, are discovered by the research group in humans almost 20 years ago. Pioneering research suggests urolithins as pleiotropic bioactive contributors to explain the health benefits after consuming ellagitannin‐rich sources (pomegranates, walnuts, strawberries, etc.). Here, this study comprehensively updates the knowledge on urolithins, emphasizing the review of the literature published during the last 5 years. To date, 13 urolithins and their corresponding conjugated metabolites (glucuronides, sulfates, etc.) have been described and, depending on the urolithin, detected in different human fluids and tissues (urine, blood, feces, breastmilk, prostate, colon, and breast tissues). There has been a substantial advance in the research on microorganisms involved in urolithin production, along with the compositional and functional characterization of the gut microbiota associated with urolithins metabolism that gives rise to the so‐called urolithin metabotypes (UM‐A, UM‐B, and UM‐0), relevant in human health. The design of in vitro studies using physiologically relevant assay conditions (molecular forms and concentrations) is still a pending subject, making some reported urolithin activities questionable. In contrast, remarkable progress has been made in the research on the safety, bioactivity, and associated mechanisms of urolithin A, including the first human interventions. About 20 years ago, urolithins are discovered as bioavailable metabolites produced by the human gut microbiota from ellagitannins and ellagic acid. Pioneering investigations suggested pleiotropic effects for urolithins that growing evidence confirms, especially for urolithin A. Here, we update the knowledge on urolithins metabolism, bioactivity, and associated gut microbiota, emphasizing the literature published in the last 5 years.